2015
DOI: 10.1097/dad.0000000000000241
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Mutation Profiling in Primary Cutaneous Melanoma

Abstract: The authors analyzed 10 somatic mutations in the main subtypes of primary cutaneous melanomas from the western region of Turkey. Mutations were found in 64.2% of the melanomas overall. The most common mutations were in the BRAF and NRAS genes. In addition to other less common mutations, a notable number of multiple mutations were encountered. The multiplicity and concurrence of mutations in this study may provide further study areas for personalized targeted therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 55 publications
5
23
2
1
Order By: Relevance
“…However, the rate of BRAF V600K mutation found was higher than that in most of the previously-reported results (Table II) (1,6,10,17). It should be noted that data gathered from closer geographical regions to that of the present study showed similar results, including higher rates of V600K mutations (15,18,19). The difference in the rate of V600K mutations may be due to the sequencing method (sequencing the entire exon 15 genome) used in other studies.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…However, the rate of BRAF V600K mutation found was higher than that in most of the previously-reported results (Table II) (1,6,10,17). It should be noted that data gathered from closer geographical regions to that of the present study showed similar results, including higher rates of V600K mutations (15,18,19). The difference in the rate of V600K mutations may be due to the sequencing method (sequencing the entire exon 15 genome) used in other studies.…”
Section: Discussionsupporting
confidence: 67%
“…Although it is said that the BRAF V600K mutation is rare, a few recent papers report higher rates of this mutation (20 to 44%) in some populations (6)(7)(8)15). In the present study, the BRAF V600E mutation was the most common subtype of the BRAF gene, followed by the BRAF V600K mutation.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…It is associated with male gender, young age, trunk localization and intermittent sun exposure [9] . Although not conclusive, it was suggested to be linked with rapid progression, poor RFS and short disease-specific survival (DSS) in several independent post-resection stage III melanoma data sets [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, his tumour harbors BRAF mutation, which is the most common oncogenic mutation in melanoma and frequently seen in nodular and superficial spreading melanoma [9] .…”
Section: Discussionmentioning
confidence: 99%